Subgrade Soil Improvement Using Local Domato (Limestone) Material from North Sulawesi - Hombokau, Chris; Pangemanan, Novriana; Mait, Rudolf; Kabo, Don (PT FORMOSA CENDEKIA GLOBAL, 2024)
Damaged and potholed roads are often caused by poor subgrade conditions. Clay subgrade cannot withstand the loads applied on it, leading to the deterioration of the pavement structure. Soil stabilization is one way to address poor subgrades. Stabilization can be done by compacting the soil or mixing it with other materials that can improve its properties. This research aims to determine the effect of mixing domato on the soil at the Final Waste Disposal Site (TPA) in Pandu Village, which is clayey, by looking at the increase in the CBR (California Bearing Ratio) value of the clay soil after stabilization with domato. This research was conducted in the soil testing laboratory of the Civil Engineering Department at Manado State Polytechnic using experimental methods by stabilizing the existing soil with the addition of sand with variations of 10%, 15%, and 20%, and testing based on ASTM (American Society For Testing and Materials) and AASHTO (American Association Of State Highway and Transportation Officials) standards. The soil samples for testing were taken from TPA Pandu, and domato was sourced from the Talaud Islands, North Sulawesi. After testing, the original soil CBR value was found to be 3.70% without being mixed with domato. Then, after stabilization using domato with a 10% mixture variation, the CBR value was 5.20%. With a 15% domato mixture variation, the CBR value was 11.80%, and finally, with a 20% variation, the CBR value was 15.50%. From the test results, it can be seen that domato significantly affects the increase in CBR value